2011
DOI: 10.1002/gps.2735
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E genotype‐specific short‐term cognitive benefits of treatment with the antihypertensive nilvadipine in Alzheimer's patients—an open‐label trial

Abstract: In this open-label trial, among APOE ε4 non-carriers, we observed stabilization of cognition and improvement in executive function among treated individuals compared with non-treated individuals. Among APOE ε4 carriers, cognitive stabilization was evident for treated individuals whereas a cognitive decline was observed in non-treated individuals. These findings provide additional evidence for potential therapeutic efficacy of nilvadipine in treating AD and warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…Interestingly, nilvadipine, but not amlodipine, has been shown to improve cerebral blood flow and cognitive function, and to reduce the rate of conversion to AD in patients with mild cognitive impairment (10). Moreover, in an open-label safety and tolerability trial with nilvadipine in AD patients, we observed that cognition was stabilized in AD patients treated with nilvadipine, whereas untreated subjects showed cognitive decline (49).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Interestingly, nilvadipine, but not amlodipine, has been shown to improve cerebral blood flow and cognitive function, and to reduce the rate of conversion to AD in patients with mild cognitive impairment (10). Moreover, in an open-label safety and tolerability trial with nilvadipine in AD patients, we observed that cognition was stabilized in AD patients treated with nilvadipine, whereas untreated subjects showed cognitive decline (49).…”
Section: Discussionmentioning
confidence: 75%
“…To our knowledge, these two DHPs represent the first small molecules identified so far that are able to stimulate the clearance of Aβ across the BBB. These data may explain why nilvadipine and nitrendipine have shown beneficial effects in AD patients (7,8,10,49). Since the efficacy of nilvadipine and nitrendipine toward Aβ accumulation is independent of their antihypertensive effect, as other antihypertensive DHPs are inefficient, we hypothesize that compounds derived from the chemical structure of Aβ-lowering DHPs could be optimized to negate their antihypertensive activity, and at the same time, enhance their Aβ-lowering properties, providing a new class of AD medications.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a short treatment duration with nilvadipine in AD patients has been shown to reduce cognitive decline (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Among the dihydropyridine CCB tested, we identified nilvadipine for its ability to readily cross the BBB, to lower brain A␤ levels, to improve cognition, and to prevent cerebral blood flow deficits in a transgenic mouse model of AD overexpressing A␤ (18,20). Nilvadipine is a clinically used antihypertensive that we have shown to be well tolerated and to stabilize cognition in AD patients compared with untreated patients (21,22). Interestingly, long term use of nilvadipine in subjects with mild cognitive impairment has also been shown to prevent cognitive decline and to reduce the incidence of AD conversion (23) suggesting that nilvadipine may have disease-modifying benefits.…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
“…Clinical investigations also showed that nilvadipine can prevent cognitive decline of patients with mild cognitive impairment [103,105]. Among non-APOE4 carriers, nilvadipine also improved short-term cognitive functions [106]. Another dihydropyridine CCB, isradipine, conferred neuroprotective effects in vitro [107], and also attenuated the levels of hyperphosphorylated tau and suppressed autophagy of tau [108].…”
Section: Antihypertensive Drugsmentioning
confidence: 96%